Dispersive Liquid-Liquid Microextraction Based on Solidification of Floating Organic Drop Followed by Gas Chromatography-Electron Capture Detector for Determination of Some Pesticides in Water Samples. (16th November 2011) - Bashiri Juybari, Mostafa; Mehdinia, Ali; Jabbari, Ali; Yamini, Yadollah
Abstract : In this study dispersive liquid-liquid microextraction based on solidification of floating organic drop (DLLME-SFO) followed by gas chromatography-electron capture detection (GC-ECD) was developed for determination of some pesticides in the water samples. Some important parameters, such as type and volumes of extraction and disperser solvent and salt effect on the extraction recovery of analytes from aqueous solution were investigated. Under the optimum conditions (extraction solvent: 1-undecanol, 15.0 μ L; disperser solvent: acetone, 1.0 mL, and without salt addition), the preconcentration factors were obtained ranged from 802 to 915 for analytes. The linear ranges were from 0.05 to 100 μ g L −1, and detection limits ranged from 0.05 to 0.008 μ g L −1 . The relative standard deviations (RSDs%, n = 5 ) were between 3.2% and 6.7%. The proposed method was successfully applied to the determination of target analytes in the tap, sea, and river water samples, and satisfactory recoveries were obtained.